International Partnerships for Strengthening Health Care Workforce Capacity: Models of Collaborative Education - William Van Cleve (Frontiers Research Topics, 2018)
A critical problem in resource-scarce countries across the globe is the shortage of appropriately trained health care providers. According to the World Health Organization, the current global health workforce shortage of 7.2 million providers is estimated to increase to 12.9 million by 2035. This disproportionately affects resource-scarce countries, denying basic health care to millions and limiting access to life-saving treatments. Due to limited resources in these countries, not enough health professionals receive training, few have the opportunity for continuing education, and the ability to develop or implement educational programs and curricula is constrained. Additionally, many existing providers choose to emigrate in pursuit of professional advancement opportunities, contributing to the overall shortage of qualified health care providers in these environments. Efforts to strengthen health workforce capacity not only increases access, safety and availability of care, but is critical to building resilient health systems capable of caring for the world's neediest populations. This requires not only cultivating new health care providers, but also providing ongoing professional development to retain and support current providers, advancing the level of practice in accordance with current clinical science, cultivating educators, and enhancing training curricula. It is critical also to contribute to the limited body of research documenting the effectiveness and impact of various models of collaborative education and partnership to improve health worker training and retention. This Research Topic examines strategies for building health workforce capacity through the prism of educational partnerships, offering significant examples of effective models of international collaborative education as well as insight and guidance on the structure and operation of successful global partnerships. Collectively, the 31 articles accepted and included in this eBook represent a diversity of health professions and geographies across academic, non-governmental organizations and other global partnership forms. The published manuscripts highlight various elements of partnerships with several consistent themes emerging: capacity building, local empowerment, mutual trust and respect, long-term commitment, equity, collaboration, and the importance of integrating theory and practice, for a balance of academic and clinical development. The manuscripts provide examples of partnership and educational programs that are in the formative, early stages of implementation and others which have been sustained long term, some for decades. The following eBook is divided into two parts, with each part broken down into sections. Part I of the eBook includes 18 manuscripts that showcase long-term educational programs that strongly exemplify multiple, foundational aspects of international partnerships in education including mutual collaboration and project management, empowerment of host partners to lead and sustain programs, and capacity building. While individual manuscripts included in Part I look broadly at multiple aspects of successful, international partnerships in education, Part II manuscripts focus intently on one-two elements. Part II includes 13 articles that highlight partnership through short- rather than long-term educational initiatives as well as program development and broad academic partnerships. This Research Topic was sponsored by Health Volunteers Overseas - a United States based non-profit that collaborates with over eighty international universities and health institutions to send volunteer health professionals to low-resource countries to provide continuing education, train the trainer courses, professional support, and consultation on academic program and curricula development.